Pengalaman Keluarga Merawat Pasien Kanker yang Menjalani Kemoterapi: Studi Kualitatif - Fazriana, Erlina; Marpiyani, Vina (PT Karya Inovasi Berkelanjutan, 2025)
Introduction & Methods Lung cancer and chemotherapy have negative impacts on both the physical and psychological well-being of patients and their caregiving families. Families often experience anxiety, fear, sadness, and burdens both physically and mentally. This study aimed to explore the experiences of families in providing care for patients undergoing chemotherapy in the Dahlia Chemotherapy Ward of Dr. H. A. Rotinsulu Pulmonary Hospital. This study employed a qualitative method with a phenomenological approach. Data were collected using purposive sampling and snowball techniques from four participants through in-depth interviews. Data analysis was conducted using Colaizzi’s seven-step method. Results The analysis identified nine major themes and seven sub-themes: (1) family knowledge about the patient’s illness and treatment; (2) changes in family roles; (3) family support for patients, with sub-themes: (a) psychological support and (b) physical support; (4) family responses while caring for patients; (5) various care strategies undertaken by families, with sub-themes: (a) utilization of health facilities, (b) use of traditional medicine, (c) fulfillment of basic patient needs; (6) patient complaints following chemotherapy; (7) challenges encountered during caregiving; (8) emergence of family burdens, with sub-themes: (a) financial burden and (b) physical and psychological burden; (9) family expectations regarding the care process. Conclusion & Recommendations This study highlights the importance of education, family assistance, and effective care coordination to support families in caring for chemotherapy patients. The findings emphasize the need to strengthen family support systems through continuous education, psychosocial assistance, and more comprehensive health service coordination. Interventions designed to improve family knowledge, adaptive capacity, and access to resources can help reduce caregiving burdens while enhancing the quality of life of both patients and their families. Contribution to the Sustainable Development Goals (SDGs) This study contributes to the Social Development Pillar of Indonesia’s Sustainable Development Goals (SDGs), specifically Goal 3: Ensure healthy lives and promote well-being for all at all ages. The targeted indicator is 3.4, which aims by 2030 to reduce premature mortality from non-communicable diseases by one-third through prevention and treatment, and to promote mental health and well-being, with specific relevance to indicator 3.4.1(a) on mortality from cardiovascular disease, cancer, diabetes, or chronic respiratory disease.